2021
DOI: 10.1371/journal.pone.0255054
|View full text |Cite
|
Sign up to set email alerts
|

A tightly clustered hepatitis E virus genotype 1a is associated with endemic and outbreak infections in Bangladesh

Abstract: Background Hepatitis E virus (HEV) infection is endemic in Bangladesh and there are occasional outbreaks. The molecular characteristics and pathogenesis of endemic and outbreak HEV strains are poorly understood. We compared the genetic relatedness and virulence associated mutations of endemic HEV strains with outbreak strains. Methods We analyzed systematically collected serum samples from HEV immunoglobulin M (IgM) positive patients attended at Bangabandhu Sheikh Mujib Medical University, Dhaka from August … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Our in vitro results regarding the potential role of these two mutations in viral pathogenicity and FHF are further corroborated by a recent study in which 21 HEV-1 whole-genome sequences were obtained from HEV IgM-positive patients from 2013 to 2015 in Bangladesh. These tightly clustered HEV strains were associated with HEV outbreaks and FHF/ALF ( 33 ). Remarkably, we found that the two unique amino acid mutations (A317T and V1120I) simultaneously occurred in 100% of all 21 HEV-1 genomes derived from FHF patients during HEV outbreaks from 2013 to 2015 in Bangladesh ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our in vitro results regarding the potential role of these two mutations in viral pathogenicity and FHF are further corroborated by a recent study in which 21 HEV-1 whole-genome sequences were obtained from HEV IgM-positive patients from 2013 to 2015 in Bangladesh. These tightly clustered HEV strains were associated with HEV outbreaks and FHF/ALF ( 33 ). Remarkably, we found that the two unique amino acid mutations (A317T and V1120I) simultaneously occurred in 100% of all 21 HEV-1 genomes derived from FHF patients during HEV outbreaks from 2013 to 2015 in Bangladesh ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2 and 3 ). Importantly, these same two unique mutations simultaneously occurred in 100% of 21 tightly clustered HEV-1 strains detected in outbreaks from Bangladesh, which are associated with FHF in patients ( 33 ). Furthermore, we demonstrated that a combinational mutant containing A317T/I1120I double mutations significantly increased HEV replication efficiency than either mutation alone ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The study that revealed 29 small HEV outbreaks (≥ 2 laboratory-confirmed cases) identified from a single private laboratory suggests that the actual burden of HEV infection in Bangladesh is much more significant than previously described by WHO using data from large outbreaks alone [ 19 ]. Strains of HEV-1a are dominant in Bangladesh and are associated with endemic outbreaks of HEV infection [ 59 ], while the 2018 Chattogram outbreak was caused by HEV-1f [ 60 ]. When compared with HEV-1a strains from India, Nepal, Pakistan, and Myanmar; within genotype 1a cluster, Bangladesh HEV strains formed a separate cluster with the 2010 HEV outbreak strains from northern Bangladesh; about 100% of the strains had A317T, T735I, L1120I, L1110F, P259S, V1479I, G1634K mutations associates AVH, FHF and RTF [ 59 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…Strains of HEV-1a are dominant in Bangladesh and are associated with endemic outbreaks of HEV infection [ 59 ], while the 2018 Chattogram outbreak was caused by HEV-1f [ 60 ]. When compared with HEV-1a strains from India, Nepal, Pakistan, and Myanmar; within genotype 1a cluster, Bangladesh HEV strains formed a separate cluster with the 2010 HEV outbreak strains from northern Bangladesh; about 100% of the strains had A317T, T735I, L1120I, L1110F, P259S, V1479I, G1634K mutations associates AVH, FHF and RTF [ 59 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…Hepatitis E virus (HEV) is a major cause of acute hepatitis around the world, but with a disproportionately high burden in low-income countries, where pregnant women and their offspring are at particular risk of severe disease and death due to HEV genotype 1 in particular [1]. This genotype is common in many low-income countries such as Bangladesh [2], while genotypes 3 and 4 dominate in high-and middle-income countries [1]. Several public health interventions, including a new vaccine [3], could probably alleviate some of the burden.…”
Section: Introductionmentioning
confidence: 99%